Representation of Surrounding Communities in Iwan Simatupang's RT-Nol/RW-Nol Drama Script (Sociology of Literature Theory) - Shofiyuddin, Haris; Wijaya, Guntur Sekti (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
This research examines the play script by Iwan Simatupang entitled RT-Nol / RW-Nol using the sociology of literature theory by Alan Swingewood and Diana Laurenson and the literary research method by Moleong. The problems are the forms of injustice that some people accept and the social criticism that the playwright tries to construct through words. This drama script reflects the real life of the lower or suburban community in big cities in Indonesia. The main focus revolves around the problem of homeless and beggars who do not have a home and do not have a steady income. The playwright does not merely write a literary work for audiences to read. Still, the writer of RT-Nol / RW-Nol has a hidden intention to make the readers aware that some parts of lives need to be improved to not further create globalization residues in human beings. The playwright also tries to criticize several systems operating in a society where the system is not or has not been under the norms of society. This discussion resulted in several conclusions, one of which is that a rule can be played. Furthermore, there is criticism regarding the injustice of the social system, which has led to the emergence of homeless people and beggars in especially big cities. Then there is the problem of income resulting from unrighteous and unethical ways. Even from that income, a human can buy a social title so the surrounding community increasingly sees it. The last conclusion is regarding words and actions that should be harmonious. Sometimes words are needed, but more than words are required to convince someone. A woman needs certainty, and a man needs to work to build self-esteem. Keywords: surrounding communities, social criticism, sociology of literature